The making of biblical womanhood : how the subjugation of women became gospel truth - Barr, Beth Allison, 1975- (Grand Rapids, MI. Brazos Press, 2021)
"A trusted historian shows that "biblical womanhood" isn't biblical, but was born in a clearly definable historical moment, and presents a better way forward for the contemporary church"--
Includes bibliographical references (pages 219-244).
Keywords: Women -- Religious aspects -- Christianity -- History of doctrines; Sex role -- Religious aspects -- Christianity -- History of doctrines..; Women -- Biblical teaching; Sex role -- Biblical teaching